Poziome wyrównywanie dochodów jednostek samorządu terytorialnego - Kańduła, Sławomira (Horizontal Equalization of Local Government's Revenues, 2009)
The aim of this article is to present the mechanisms of horizontal budgetary redistribution among local government units. The study attempts also at the evaluation of this redistribution as a form of financing local government units. In particular, the article discusses the reasons of horizontal redistribution, the ways of calculating payments to central budget which are shared as transfers among local government units and the scale of this equalization in Poland between 1996 and 2007
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 76-88